THE ANALYSIS OF THE EFFECT OF ENHANCEMENT VILLAGE STATUS (THE VILLAGE BUILDING INDEX) ON REDUCTION THE POVERTY RATE IN THE PROVINCE OF WEST KALIMANTAN - Sunaryono Sunaryono (Jurnal Ekonomi dan Manajemen, 2021)
Village Building Index (IDM) is a measuring instrument issued by the Ministry of Villages & PDTT to measure the success of development and use of Village Funds in a village. This measuring instrument includes 50 indicators divided into three large groups, namely The Social Resilience Index (IKS), The Economic Resilience Index (IKE), and The Environmental Resilience Index (IKL). The three groups have the same score in measurement and will determine the status of a village. The village's class divide into five categories that are very lagging, lagging, developing, advanced, and independent. Based on the measurement, the village level with a maximum score will have the independent level and get autonomous status while still low in scoring will achieve a very lagging status. This study aims to determine the dorp level score to reduce the poverty rate in the village. Because the rise should follow the increasing IDM status of a town in a village's social and economic classes, this village's position makes the villagers' rising economy. The growing economy of the villagers should help reduce the poverty rate in the town.